2022
DOI: 10.3389/fbioe.2022.1025155
|View full text |Cite
|
Sign up to set email alerts
|

An oral delivery vehicle based on konjac glucomannan acetate targeting the colon for inflammatory bowel disease therapy

Abstract: Orally administered colon-targeted delivery vehicles are of major importance in the treatment of inflammatory bowel disease (IBD). However, it remains a challenge to maintain the integrity of such delivery vehicles during treatment, particularly in the gastric environment, which may cause untimely drug release before reaching the targeted colon. Herein, an oral colon-targeted drug delivery system (OCDDS) based on acetylated konjac glucomannan (AceKGM) has been developed in this work, which accomplishes colonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Wang et al developed a naturally occurring polysaccharide-based NP that targets binding to macrophage mannose receptors. 75 According to the experimental results, NPs exhibited 81% drug release within 48 h, and the MPO levels of the mice were decreased. The NPs offer sustained release of curcumin and effective therapeutic outcomes compared to oral free curcumin administration ( Figure 6 ).…”
Section: Active Targetingmentioning
confidence: 95%
See 1 more Smart Citation
“…Wang et al developed a naturally occurring polysaccharide-based NP that targets binding to macrophage mannose receptors. 75 According to the experimental results, NPs exhibited 81% drug release within 48 h, and the MPO levels of the mice were decreased. The NPs offer sustained release of curcumin and effective therapeutic outcomes compared to oral free curcumin administration ( Figure 6 ).…”
Section: Active Targetingmentioning
confidence: 95%
“…It also increases the degree of endocytosis and the bioadhesion of drug agents to particular cells ( Figure 1F ). 75–94 …”
Section: Active Targetingmentioning
confidence: 99%
“…This study used an ex vivo murine colonic explant from an inflammation model and found that NPL/Cur is not only on the surface of epithelial cells, but also can penetrate into the intestinal wall, with stronger targeting (Salah et al, 2022). Curcumin encapsulated by solid binary lipid nanoparticles (C-SBLNs) also has good gastrointestinal stability, and prolonged drug release up to 24 h. Oral administration of C-SBLNs can reduce leukocyte infiltration, oxidative stress and proinflammatory cytokines (TNF-α), restore colon structure in DSS-induced colitis mice (Sharma et al, 2019) (Wang et al, 2022). Drug delivery systems based on pH and/or enzyme also have good application prospects in IBD.…”
Section: Nps For the Delivery Of Curcuminmentioning
confidence: 99%
“…At 48 h, the release of Cur-AceKGM NPs in SIF can reach 81%. Cur-AceKGM NPs can decrease the colon local level of MPO and DAI score, significantly alleviate the symptoms of colitis ( Wang et al, 2022 ). Drug delivery systems based on pH and/or enzyme also have good application prospects in IBD.…”
Section: Application Of Synthetic Nanoparticles Loaded With Medicinal...mentioning
confidence: 99%